2016
DOI: 10.1108/oir-12-2015-0378
|View full text |Cite
|
Sign up to set email alerts
|

Hashtags and information virality in networked social movement

Abstract: Purpose -The purpose of this paper is to conceptualize the use of Twitter hashtag as a strategy to enhance the visibility and symbolic power of social movement-related information. It examined how characteristics of hashtag drove information virality during a networked social movement. Design/methodology/approach -Twitter data from two days during the Occupy Wall Street Movement in 2011 were collected. With network analysis, the authors identified popular hashtag types and examined hashtag co-occurrence patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 41 publications
1
73
0
4
Order By: Relevance
“…Organizing is the second motivation we identified from our data. Considering that the original purpose of hashtags is to structure and organize the content of posting (e.g., Wang et al, ), it is not surprising that organizing is one of the more common motivations for using hashtags. In addition to structuring the internal content of postings, this motivation encompasses the broader understanding of organizing one’s own social media participation, including showing and linking other related content areas and organizing own postings around topics (e.g., events and places).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Organizing is the second motivation we identified from our data. Considering that the original purpose of hashtags is to structure and organize the content of posting (e.g., Wang et al, ), it is not surprising that organizing is one of the more common motivations for using hashtags. In addition to structuring the internal content of postings, this motivation encompasses the broader understanding of organizing one’s own social media participation, including showing and linking other related content areas and organizing own postings around topics (e.g., events and places).…”
Section: Discussionmentioning
confidence: 99%
“…The Twitter support page (2018) explains the features of hashtags in terms of the way they permit users to “index keywords or topics” of their own content and “to easily follow topics they are interested in.” Thus, Twitter recommends that people use the pound symbol “before a relevant keyword or phrase in their Tweet to categorize those tweets and help them show more easily in Twitter search.” This is because “[c]licking or tapping on a hashtagged word in any message shows you other tweets that include that hashtag”; in addition, hashtagged words can result in promoted topics, termed “trending topics.” Not surprisingly, using popular hashtags can increase postings’ reach (Wang et al, ) and allows users to identify postings related to topics of their interest (Jackson & Foucault Welles, ). These popular features of hashtags have triggered their wide adoption by many other popular social media platforms, including Facebook, Instagram, LinkedIn, and WeChat.…”
Section: Hashtags: Theory and Prior Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Visibility is crucial to achieving symbolic power, defined as "the capacity to intervene in the course of events and influence the actions of others by means of the production and transmission of symbolic forms" [13]. In [14] it was showed that self-organized movement participants used strategies to leverage social media to better diffuse their message and enhance their symbolic power by combining the use of different hashtags to reach distinct social circles.…”
Section: Introductionmentioning
confidence: 99%